Thyroid remnant volume and Radioiodine ablation in Differentiated thyroid carcinoma (Bangladesh Journal of Nuclear Medicine, 2015)
Aims: The aims of the study were to determine the thyroid remnant volume and to see the effect of radioiodine ablation on thyroid remnant volume. Methods: A retrospective analysis of seventy-one differentiated thyroid carcinoma patients treated with high dose radioiodine (I-131) for post surgical ablation of thyroid remnants were done in Institute of Nuclear Medicine & Allied Sciences, Comilla of Bangladesh Atomic Energy Commission. Female were 60 and male were 11 with female-male ration of 5.5:1. All patients enrolled during the period from January 2001 to December 2011. The age range of the patients was 15 years to 90 years. The thyroid remnant volumes were determined by SPECT scintigraphy. High dose radioiodine (I-131) ablations were done with doses ranged from 2.77 GBq (75mCi) to 5.55 GBq (175 mCi). A successful ablation was defined as the absence of activity in the thyroid bed on subsequent imaging studies. Results: Fifty-nine patients (83.1%) showed complete ablation and twelve (16.9%) showed partial ablation of thyroid remnants after radioiodine therapy. The remnant thyroid volume as determined from scintigraphic images was significantly different (p = 0.048) between them who were completely ablated and them who were partially ablated. It was also observed that in complete ablation, 52.5% had thyroid remnant volume 3.0 gm. i.e., The smaller the volume of thyroid remnant, better the response and larger the volume, the poorer the response to radioiodine. Conclusions: Successful ablation of thyroid remnants significantly depends on their volume and the successful ablation is inversely related with thyroid remnant volume. DOI: http://dx.doi.org/10.3329/bjnm.v17i1.22492 Bangladesh J. Nuclear Med. 17(1): 55-60, January 2014